Severity and impact of acne vulgaris on the quality of life of adolescents in Nigeria - Ogedegbe EE; Henshaw EB (Clinical, Cosmetic and Investigational Dermatology, 2014)
Evelyn E Ogedegbe,1 Eshan B Henshaw2 1Cedarcrest Hospital, Abuja, Federal Capital Territory, Nigeria; 2Department of Medicine, Faculty of Medicine and Dentistry, University of Calabar, Cross River State, Nigeria Background: Acne vulgaris is a common skin condition, which affects most adolescents at some point in their lives. It has been found to have a significant impact on their psychological well-being and has been associated with depression and suicide ideation. Many studies have assessed the impact of acne vulgaris on the quality of life (QoL) in different population subgroups around the world, but there is a dearth of reports from the African subcontinent. This study thus seeks to assess the severity of acne vulgaris and determine its effect on the QoL of adolescents in Lagos, Nigeria. Methods: In a cross-sectional survey employing a two-stage sampling method, the severity of acne vulgaris and its impact on the QoL of adolescents attending a senior secondary school in Lagos, Nigeria was assessed using the Global Acne Grading Scale (GAGS) and the Cardiff Acne Disability Index (CADI), respectively. The correlation between the results of the GAGS and CADI was also determined. Results: One hundred and sixty adolescent students with acne were recruited, with males accounting for 51.9% and females 48.1%. The mean and standard deviation of the GAGS severity scores were 11.3±5.4 for males and 11.9±5.4 for females. Only one student had severe acne vulgaris (GAGS, 31–38), 10% moderate (GAGS, 19–30), and 89.4% mild (GAGS, 1–18). The overall CADI score was 3.4±3.0, which suggests mild impairment in QoL; however, the solitary student with severe acne had severe QoL impairment. There was a weak positive correlation between the GAGS and the CADI score. Conclusion: Most adolescents in our study had mild acne vulgaris, and the overall impact on their QoL was mild. However, the correlation between the psychosocial impact and acne severity was weak. There is a need for similar studies in other parts of the country and for further studies to determine the adequacy of the existing instruments in assessing the impact of acne vulgaris in Nigerian adolescents. Keywords: CADI, GAGS, skin disease, teenage dermatosis, psychosocial impact